KEPALA MADRASAH SEBAGAI MOTIVATOR - Ibrahim, Ibrahim; Marhama, Marhama; Alya, Nabilah (UIN Imam Bonjol Padang, 2023)
This article pertains to the Head of Madrasah as a Motivator at MA Nurul Muhajirin Sukatani, with the aim of examining the role of the madrasah head as a motivator. This research employs a qualitative method and a descriptive approach. Data is collected through interviews, observations, and document analysis. Subsequently, the data is analyzed through the stages of data reduction, data presentation, and data verification. To ensure data validity, data triangulation is utilized, which includes source triangulation, method triangulation, and technique triangulation. Based on the results and discussions outlined above, it can be concluded that the madrasah head at MA Nurul Muhajirin Sukatani-Tanjung Lago-Banyuasin-South Sumatra has effectively fulfilled their role and responsibilities as a leader. As a leader, they have provided motivation to all stakeholders involved in education, especially educators. There are four key activities carried out by the madrasah head in their role as a motivator, namely articulating an inspiring vision and mission for the madrasah, providing support to educators and the education sector, promoting collaboration among various elements within the madrasah, and implementing innovations in the field of education to ensure that education remains relevant, effective, and beneficial for students. Innovations in education enable the madrasah to overcome existing challenges and keep up with positive developments in the field of education.